A Closer Examination of the Relationship between Religiosity and Problematic Pornography Viewing in Heterosexual Men. Issue 1 (2nd April 2020) - Borgogna, Nicholas C.; Isacco, Anthony; McDermott, Ryon C.
Abstract: Problematic pornography viewing is a considerable issue for religious men. We tested a conceptual model positing scrupulosity and self-compassion as simultaneous mediators of the relationship between religiosity and problematic pornography viewing. We additionally examined the combined contributions of traditional masculinity ideology, pornography viewing frequency, spiritualty, and religious behaviors within the model. Results from 244 heterosexual men indicated scrupulosity as the only significant predictor and mediator of problematic pornography in the full model. Further, pornography viewing frequency was inversely related to scrupulosity. Our results compliment recent findings highlighting the importance of addressing religious scrupulosity in the treatment of problematic pornography viewing.